Effects of Diagnostic Tibial Nerve Block and Selective Tibial Nerve Neurotomy on Spasticity and Spastic co-contractions: A Retrospective Observational Study - Jean-Philippe Lamora; Thierry Deltombe; Thierry Gustin (Medical Journals Sweden, 2023)
Objective: To assess the effects of diagnostic nerve block and selective tibial neurotomy on spasticity and co-contractions in patients with spastic equinovarus foot. Methods: Among 317 patients who underwent a tibial neurotomy between 1997 and 2019, 46 patients who met the inclusion criteria were retrospectively screened. Clinical assessment was made before and after diagnostic nerve block and within 6 months after neurotomy. A total of 24 patients underwent a second assessment beyond 6 months after surgery. Muscle strength, spasticity, angle of catch (XV3), passive (XV1) and active (XVA) ankle range of motion were measured. The spasticity angle X (XV1-XV3) and paresis angle Z (XV1-XVA) were calculated with the knee in flexed and extended positions. Results: Tibialis anterior and triceps surae strength remained unchanged, while both Ashworth and Tardieu scores were highly reduced after nerve block and neurotomy at all measurement times. XV3 and XVA increased significantly after block and neurotomy. XV1 increased slightly after neurotomy. Consequently, spasticity angle X and paresis angle Z decreased after nerve block and neurotomy. Conclusion: Tibial nerve block and neurotomy improve active ankle dorsiflexion, probably by reducing spastic co-contractions. The results also confirmed a long-lasting decrease in spasticity after neurotomy and the predictive value of nerve blocks. LAY ABSTRACT Selective tibial nerve neurotomy is an effective surgical treatment for spastic equinovarus foot deformity after stroke. However, its effectiveness on spastic co-contractions, defined as a disabling involuntary antagonist contraction during an active agonist movement, is unknown. This retrospective study evaluated the effects of tibial neurotomy on the active ankle dorsiflexion limitation related to co- contractions. Selective tibial neurotomy allows an immediate improvement in active dorsal flexion of the ankle, probably by decreasing muscle co-contractions around this joint. This effect continues for the long term for the soleus muscle. This study also confirms that reflex spasticity is permanently reduced after neurotomy. This surgical technique therefore seems useful in limiting impairment caused by the development of spasticity and co-contractions after a stroke.